Primer group of companies business development knowledge management audit a tool for knowledge management framework development - Sebastian, Mark Harold (University of the Philippines Diliman, 2013)
Academics have debated the meaning of "knowledge" since the word was invented, but let's not get into that here. A dictionary definition is "the facts, feelings or experiences known by a person or group of people" (Collins English Dictionary). Knowledge is derived from information but it is richer and more meaningful than information. It includes familiarity, awareness and understanding gained through experience or study, and results from making comparisons, identifying consequences, and making connections. Some experts include wisdom and insight in their definitions of knowledge. In organizational terms, knowledge is generally though of as being "know how", or "actionable information". The last point is an important one. Today's organization contain a vast amount of knowledge and the company at hand is certainly no exception. However, in applying knowledge management principles and practices in our organization, knowledge is not our end, but the means for further action. What we are trying to do is to use our knowledge to get better at doing what we do. Knowledge must not be seen as something that is supplied from one person to another, or from better off countries to developing countries, but rather as something that can flow back and forth and be continually improved, adapted, and refreshed using knowledge management tools. What is more, the latter are more effective where the specific knowledge, relationships, and context of organizations and the external environment they face are dealt with in an integrated and coherent manner. Knowledge management (KM) is based on the idea that an organization's most valuable resource is the knowledge of its people. Therefore, the extent to which an organization performs well, will depend, among other things, on how effectively its people can create new knowledge, share knowledge around the organization, and use that knowledge to best effect. Knowledge management is first and foremost a management discipline that treats intellectual capital as a managed asset. The primary tools applied in the practice of knowledge management are organizational dynamics, process engineering, and technology. These work in concert to streamline and enhance the capture and flow of an organization's data, information and knowledge and to deliver it to individuals and groups engaged in accomplishing specific tasks. These individuals, or knowledge workers, are unequivocally the most vital resource in the 21st-century company. The primary goal of knowledge management is to deliver the intellectual capacity of the firm to the knowledge workers who make the day to day decision that in aggregate determine the success or failure of a business. Knowledge management is not about creating a central database that is a complete replica of all that is known by employees or that is embedded in the systems they use. On the contrary, knowledge management is about embracing a diversity of knowledge sources, from databases, Web sites, employees, and partners and cultivating that knowledge where it resides, while capturing its context and giving it greater meaning through its relation to other information in the company. Knowledge management is not about turning knowledge workers into interchangeable components by plugging them into some corporate knowledge base. The strategic importance of knowledge in today's organization has been discussed extensively and research has looked at various issues in developing knowledge management systems. Both the characterization of knowledge and alternate models for understanding the acquisition and use of such knowledge have taken on significant prominence. This is due to the complexities associated with acquiring and representing knowledge, and the varied nature of its use in knowledge work. As they say, Knowledge is Power-and profit. According to Bhandari Technologies (2010), one source of competitive advantage is to diffuse throughout a company the unique, proprietary knowledge about customers, competitors, products, and techniques that resides in the minds of its employees. But many efforts at knowledge management have failed to deliver that advantage, because they haven't focused on the creation and broad exchange of knowledge within a company. Establishing an internal knowledge market with its own unique approaches to pricing,exchange, market facilitation and competition can solve that problem and boost productivity. Now on its 27th year as an authority in retail and a major player in industrial services, the company is proud to bring in new and exciting global brands, increase doors in new territories and create new concept stores through an aggressive expansion project in the Asian region. These goals would not be turned into a reality without the business development research team's help and wisdom. It is through them those new brands that are being called and source upon are carefully studied as they are able to forecast market movements and watch trends evolve. The role of the business development research team is crucial to the business as they serve as the filter of the brands coming in it is in their hands whether much attention would be given to a specific brand or a brand would be let go off. It is this kind of decision making process where knowledge is greatly needed and relied on. Over the past years, the Primer Group of Companies has grown faster than expected. The next step to be taken largely depends on the business development team and its research team. The team since its inception two years ago was the one tasked in brand sourcing and research. It is the goal of the team to deliver and present important points that will help management in acquiring and letting go of a brand. With this tedious task at hand comes a practice that makes repetitive work as there's no system being followed in doing the assigned task. The problem has been a recurring concern not only by the team but the clients we are serving such as the brand managers and the marketing team. Idea of having a structured system remains as it is and never materialized as efforts were not that concentrated on the proposed system. The output of this project would help present the concept of knowledge management and its benefits to the team as well as assess status of critical knowledge in turn developing a conceptual framework.